Atmospheric River Brings Warmth and Rainfall to the Northern Antarctic Peninsula During the Mid‐Austral Winter of 2023 - D. Bozkurt; J. F. Carrasco; R. R. Cordero; F. Fernandoy; A. Gómez‐Contreras; B. Carrillo; B. Guan (Geophysical Research Letters)
Abstract Contrasting the extensive research on summer atmospheric rivers (ARs) in the Antarctic Peninsula (AP), winter AR impacts are less understood. This study examines a unique warming event from 1 to 3 July 2023, using in situ winter observations and ERA5 reanalysis. On 2 July, Frei station experienced an extreme warm event with a temperature of 2.7°C and a significant rise in the freezing level, coinciding with winter rainfall. A pressure dipole pattern over the AP, with contrasting circulations over Bellingshausen and Weddell Seas, facilitated an AR, carrying warm, humid air initially from South America/Atlantic and then the southeast Pacific. This shift resulted in anomalous water stable isotope composition in precipitation. Trends suggest a strengthening winter pressure dipole, associated with increased AR frequency and higher temperatures in northern AP. These findings highlight the importance of winter observations in exploring AR impacts, bridging knowledge gaps about winter AR behaviors.